2004
DOI: 10.2166/ws.2004.0050
|View full text |Cite
|
Sign up to set email alerts
|

Optimal planning model for rehabilitation of water networks

Abstract: An optimal planning model for rehabilitation of water networks is presented. Capital costs (replacement, rehabilitation and repairing costs), benefits (by the reduction of pumping cost and leakage cost), and hydraulic reliability are used for making an optimal decision for the rehabilitation plan of a water pipe network. KYPIPE is used for checking the hydraulic reliability. A multi-objective optimization model is successfully developed in this study. And the task is tackled using a new meta-heuristic algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…The methods presented by these authors allow for a systemwide analysis and prioritization of assets. Finally, examples of multi-objective formulations of the replacement planning problem are presented (Dandy & Engelhardt, 2006;Kim et al, 2004;Osman et al, 2017), which involve considerations such as cost minimization, hydraulic reliability, and impacts to road users and customers.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…The methods presented by these authors allow for a systemwide analysis and prioritization of assets. Finally, examples of multi-objective formulations of the replacement planning problem are presented (Dandy & Engelhardt, 2006;Kim et al, 2004;Osman et al, 2017), which involve considerations such as cost minimization, hydraulic reliability, and impacts to road users and customers.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…HS works with those three basic parameters (HM, HMCR and PAR) and Fig. 3 shows flowchart of HS suggested by Geem et al (2001) Paik (2001), Kim et al (2004) and Paik et al (2005) reported that changes in the HS parameters may shorten the searching time for the global optimum. Paik (2001) and Paik et al (2005) divided HS into three types, namely, type 1 (HS1), type 2 (HS2), type 3 (HS3) and suggested the MHS (Modified HS) having a different method for applying HMCR and PAR.…”
Section: Harmony Search Algorithmmentioning
confidence: 99%
“…Paik (2001) and Paik et al (2005) divided HS into three types, namely, type 1 (HS1), type 2 (HS2), type 3 (HS3) and suggested the MHS (Modified HS) having a different method for applying HMCR and PAR. Kim et al (2004) suggest the ReHS (Revised HS) using non-fixed values of HMCR and PAR to improve the searching capability for optimization of pipe rehabilitation and this approach is used in this study.…”
Section: Harmony Search Algorithmmentioning
confidence: 99%
“…Actually it is a difficult problem due to budget limitations. So, in most cases, decisions are made on when and which pipes in the system should be replaced or rehabilitated (Kim et al [8]).…”
Section: Introductionmentioning
confidence: 99%